Evaluation of The Implementation of Psak 71 Concerning Expected Credit Loss on The Consolidated Financial Statements of The Company PT Waskita Karya (Persero) Tbk - Kiki Fernando Perpetua Oroh; Lintje Kalangi; Sintje Rondonuwu (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
The Financial Accounting Standards Board Institute of Indonesia Chartered Accountants issued guidelines for responding to the COVID-19 pandemic on entity financial reports, namely the application of PSAK 71 concerning expected credit losses which was effective January 1, 2020. This study aims to :(1) determine the application of PSAK 71 regarding expected credit losses at PT. Waskita Karya Tbk (2) the impact of the application of the PSAK 71 rules on the company’s financial statements of PT. Waskita Karya Tbk. The method of analysis used in this research is a descriptive method in which the aim of each data is collected to be analyzed then draws a conclusion and the type of research used is descriptive qualitative. The results obtained that the company has implemented PSAK 71 in the 2020 reporting period with the principle of 12-month expected loss so that it has an impact on a decrease in retained earnings by 24.2% of the total decline in the company's retained earnings in 2020 and also has an impact on a decrease in total equity by 20,47% of the total equity decline in 2020.Keywords: Evaluation, Application, Expected Credit Loss